Innovative Radiopharmaceuticals in Oncology and Neurology - Michel Cherel (Frontiers Research Topics, 2017)
The aim of this Research Topic was to assemble a series of articles describing basic, preclinical and clinical research studies on radiopharmaceuticals and nuclear medicine. The articles were written by attendees of the third Nuclear Technologies for Health Symposium (NTHS, 10th-11th March 2015, Nantes, Frances) under the auspices of the IRON LabEx (Innovative Radiopharmaceuticals for Oncology and Neurology Laboratory of Excellence). This French network, gathering approximately 160 scientists from 12 academic research teams (Funded by "investissements d'Avenir"), fosters transdisciplinary projects between teams with expertise in chemistry, radiochemistry, radiopharmacy, formulation, biology, nuclear medicine and medical physics. The 12 articles within this resulting eBook present a series of comprehensive reviews and original research papers on multimodality imaging and targeted radionuclide therapy; illustrating the different facets of studies currently conducted in these domains.